Anti-Inflammatory Potential of Pteropodine in Rodents - Rogelio Paniagua-Pérez; Laura Sánchez-Chapul; Eduardo Madrigal-Bujaidar; Isela Álvarez-González; Eduardo Madrigal-Santillán; Lidia Cruz-Hernández; Carlos Martínez-Canseco; Celia Reyes-Legorreta; Lidia Ruiz-Rosano; Cecilia Hernández-Flores; Rene Valdez-Mijares; Alejandra Quintana-Armenta (Metabolites, 2023)
Pteropodine (PT) is a component of some plants with potentially useful pharmacological activities for humans. This compound has biomedical properties related to the modulation of the immune system, nervous system, and inflammatory processes. This study addresses the anti-inflammatory and antioxidant capacity of pteropodin in a murine model of arthritis and induced edema of the mouse ear. To evaluate the anti-inflammatory activity, we used the reversed passive Arthus reaction (RPAR), which includes the rat paw edema test, the rat pleurisy test, and a mouse ear edema model. The antioxidant effect of PT was evaluated by determining the myeloperoxidase enzyme activity. PT showed an anti-inflammatory effect in the different specific and non-specific tests. We found a 51, 66 and 70% inhibitory effect of 10, 20 and 40 mg/kg of PT, respectively, in the rat paw edema test. In the pleurisy assay, 40 mg/kg of PT induced a low neutrophil count (up to 36%) when compared to the negative control group, and 20 mg/kg of PT increased the content of lymphocytes by up to 28% and the pleural exudate volume decreased by 52% when compared to the negative control group, respectively. We also found an 81.4% inflammatory inhibition of the edema ear with 0.04 mg/ear of PT, and a significant myeloperoxidase enzyme inhibition by the three doses of PT tested. We conclude that PT exerted a potent anti-inflammatory effect in the acute inflammation model in rodents.